Fecal microbial signatures of healthy Han individuals from three bio-geographical zones in Guangdong - Huang, Litao; Deng, Liting; Liu, Changhui; Huang, Enping; Han, Xiaolong; Xiao, Cheng; Liang, Xiaomin; Sun, Huilin; Liu, Chao; Chen, Ling (Frontiers in microbiology, 2022)
Important forensic evidence traced from crime scenes, such as fecal materials, can help in the forensic investigation of criminal cases. Intestines are the largest microbial pool in the human body whose microbial community is considered to be the human “second fingerprint”. The present study explored the potential for community characteristics of gut microbes in forensic medicine. Fecal microbiota profiles of healthy individuals from three representative Han populations (Guangzhou, Shantou and Meizhou) in Guangdong Province, China were evaluated using High-throughput sequencing of V3-V4 hypervariable regions of the 16SrRNA gene. Results of the present study showed that at the genus level, Shantou, Guangzhou, and Meizhou behaved as Enterotype1, Enterotype2, and Enterotype3, which were mainly composed of Bacteroides, Prevotella, and Blautia, respectively. Based on OTU abundance at the genus level, using the random forest prediction model, it was found that there might be potential for distinguishing individuals of Guangzhou, Meizhou, and Shantou according to their fecal microbial community. Moreover, the findings of the microbial community of fecal samples in the present study were significantly different from that of saliva samples reported in our previous study, and thus it is evident that the saliva and feces can be distinguished. In conclusion, this study reported the fecal microbial signature of three Han populations, which may provide basic data for the potential application in forensic practice, containing body fluid identification, and geographical inference.